1996
DOI: 10.1074/jbc.271.39.24036
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Membrane-bound Rod Phosphodiesterase by the Rod Phosphodiesterase Recombinant δ Subunit

Abstract: Retinal rod and cone phosphodiesterases are oligomeric enzymes that consist of a dimeric catalytic core (␣ 2 in cones and ␣␤ in rods) with inhibitory subunits (␥) that regulate their activity. In addition, a 17-kDa protein referred to as the ␦ subunit co-purifies with the rod soluble phosphodiesterase and the cone phosphodiesterase. We report here partial protein sequencing of the rod ␦ subunit and isolation of a cDNA clone encoding it. The predicted amino acid sequence is unrelated to any other known protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 45 publications
8
84
0
1
Order By: Relevance
“…27,28 A 17-kDa prenyl binding protein (PrBP), originally referred to as the 'delta' (d) subunit of PDE6, 29 can bind to PDE6 and release the holoenzyme from its membrane-associated state. 30 PrBP principally interacts with PDE6 at its prenylated C-terminus. 31 In contrast to the catalytic and inhibitory subunits of PDE6, PrBP is widely expressed in a variety of tissues.…”
Section: S30mentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 A 17-kDa prenyl binding protein (PrBP), originally referred to as the 'delta' (d) subunit of PDE6, 29 can bind to PDE6 and release the holoenzyme from its membrane-associated state. 30 PrBP principally interacts with PDE6 at its prenylated C-terminus. 31 In contrast to the catalytic and inhibitory subunits of PDE6, PrBP is widely expressed in a variety of tissues.…”
Section: S30mentioning
confidence: 99%
“…31 In contrast to the catalytic and inhibitory subunits of PDE6, PrBP is widely expressed in a variety of tissues. 30,32 It is also highly conserved through evolution. 33 While PrBP has been shown to interact with many other binding partners, 34 neither PDE5 nor other phosphodiesterases have been reported to interact with this prenyl binding protein.…”
Section: S30mentioning
confidence: 99%
“…Yeast two hybrid studies identified two proteins interact- ing with the RCC1 domain of RPGR: the phosphodiesterase delta subunit (PDE δ) [Linari et al, 1999a;Hong et al, 2001] and a novel protein called RPGRIP1 [Boylan and Wright, 2000;Roepman et al, 2000;Hong et al, 2001]. Interestingly, PDEδ not only interacts with retinal phosphodiesterase subunits [Florio et al, 1996], but also with the small GTPases Rab13 [Marzesco et al, 1998] and Arl3 [Linari et al, 1999b].…”
Section: Biological Relevance Mutations In the Rcc1-like Domainmentioning
confidence: 99%
“…This was indeed verified by a number of biochemical and cellular studies which suggested that PDE6d is a general prenyl binding protein (therefore also called PrBP) without apparent selectivity. [33][34][35][36][37][38][39] In contrast to RhoGDI and RabGDI which are specific for the GDP-bound conformation of prenylated Rho or Rab proteins, 39,40 PDE6d binds Ras and Rheb independent of their nucleotidebound conformation. 34,41 The structure of the Arl2-PDE6d complex shows however that the hydrophobic pocket is partially occupied suggesting a mutually exclusive binding to prenylated cargo and/or Arl2.…”
Section: The Similarity Between Arl2 and Arl3mentioning
confidence: 99%